COMBINED EFFECT OF RICE HUSK ASH AND CEMENT KILN DUST AS CEMENT REPLACEMENT MATERIALS IN CONCRETE (FUDMA JOURNAL OF SCIENCES, 2020)
This study is aimed at evaluating the suitability of using ash sourced from rice husk and dust from cement kiln (RHA/CKD) as a partial replacement of conventional cement (ordinary Portland cement) in concrete with 1:2:4 and 0.55 as a mix ratio and  water cement ratio respectively.. The ash was obtained by uncontrolled burning process; the ash was cooled, grounded, and passed through a 75 microns BS sieve. The result of X-ray fluorescence (XRF) test carried out on rice husk ash RHA and Cement Kiln Dust CKD indicates that the RHA has higher content of silicon oxide when compared with CKD, while CKD has higher content of calcium oxide compared with RHA. Cement was replaced with 0 %, 10 %, 20 %, 30 %, 40 % and 50 % of combined RHA/CKD and 100 mm cube Concrete cubes were cast and cured in water for 7, 14, and 28 days. The result of workability showed that as the RHA/CKD content increased the workability (slump) decreased, but setting times, consistency and soundness of RHA/CKD-cement paste increased with RHA/CKD content increase; also, the compressive strength of RHA/CKD based concrete increases with age, and with RHA/CKD content up to 20 % cement replacement at 28 days, then gradually decreases. It was concluded that the optimum blend of RHA/CKD as cement replacement in concrete should not be more 20 % replacement.
Keywords: Rice husk ash (RHA), Cement kiln dust (CKD), workability, compressive strength, pozzolana